Mechanisms of Fast Ripples in the Hippocampus - Dzhala, Volodymyr I. (J Neurosci, 2004)
Hippocampal fast ripples (FRs) have been associated with seizure onset in both human and experimental epilepsy. To characterize the mechanisms underlying FR oscillations (200-600 Hz), we studied activity of single neurons and neuronal networks in rat hippocampal slices in vitro. The correlation between the action potentials of bursting pyramidal cells and local field potential oscillations suggests that synchronous onset of action potential bursts and similar intrinsic firing patterns among local neurons are both necessary conditions for FR oscillations. Increasing the fidelity of individual pyramidal cell spike train timing by blocking accommodation dramatically increased FR amplitude, whereas blockade of potassium conductances decreased the fidelity of action potential timing in individual pyramidal cell action potential bursts and decreased FR amplitude. Blockade of ionotropic glutamate receptors desynchronized onset of action potential bursts in individual pyramidal cells and abolished fast ripples. Thus, synchronous burst onset mediated by recurrent excitatory synaptic transmission and similar intrinsic spike timing mechanisms in neighboring pyramidal cells are necessary conditions for FR oscillations within the hippocampal network.